Studi Evaluatif Terhadap Materi dan Dasar Hukum Pemberlakuan Kompilasi Hukum Islam - Suma, Muhammad Amin (Unisia, 2016)
There are, at least two weaknesses of the compilation of Islamic law (KHI); first, matenally and second, legally. Although the legal status KHI is still disputed-as the legalization through presidential decree is not as strong as regulation (UU), the material weaknesses are much more important. There are material contents that need to be reactualized. This because many changes happen within the development of Moslemsocieties. So, as a legal instrument. KHI need to accommodate such changes.